2018
DOI: 10.1038/s41598-018-32851-y
|View full text |Cite
|
Sign up to set email alerts
|

ERK activating peptide, AES16-2M promotes wound healing through accelerating migration of keratinocytes

Abstract: Wound healing is an important issue that influences quality of life, and the need for products associated with wound healing is growing annually. New materials and therapies for skin wounds are being continuously researched and developed in order to increase treatment efficacy. Here, we show that the peptide AES16-2M comprised of five short amino acid sequences (REGRT) demonstrates efficacy in wound healing. AES16-2M exerted more effective healing than the control in an acute wound model, and tissue regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
3
29
1
Order By: Relevance
“…In the treatment of CAPJ focusing in the central zone of the wound, the residual plasma gas may diffuse and influence on the margin of the wound edge, thereby inducing keratinocyte migration as well. In addition, the histological examination showed that keratinocyte migration could be activated to improve the wound healing by diminishing the wound size (Figure 7, day 14, He + Ar treatment group), which was consistently with previous studies (Lee et al, 2018;Zhang et al, 2019). Taken together, the in vitro study showing the keratinocyte activation can be histologically observed in the in vivo study and accompanying with muscular contraction that provide evidence for the underlying mechanisms of CAPJ to promote wound healing.…”
Section: Discussionsupporting
confidence: 88%
“…In the treatment of CAPJ focusing in the central zone of the wound, the residual plasma gas may diffuse and influence on the margin of the wound edge, thereby inducing keratinocyte migration as well. In addition, the histological examination showed that keratinocyte migration could be activated to improve the wound healing by diminishing the wound size (Figure 7, day 14, He + Ar treatment group), which was consistently with previous studies (Lee et al, 2018;Zhang et al, 2019). Taken together, the in vitro study showing the keratinocyte activation can be histologically observed in the in vivo study and accompanying with muscular contraction that provide evidence for the underlying mechanisms of CAPJ to promote wound healing.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that there is still a significant contribution of pro-inflammatory cytokines in healthy tissues spatially removed from the joint. p-HSP27, p-AKT, and p-ERK1/2 have all been linked to early proliferative wound healing responses in trauma [55] and skin wounds [56]. Their low radiality outcomes suggested that these three phosphoproteins may be driving the tissue healing response.…”
Section: Discussionmentioning
confidence: 99%
“…In a final set of experiments, the role of activation of ERK signaling in cell migration was investigated. ERK phosphorylation can be inhibited using specific MEK inhibitors such as U0126 22 . ERK activation after wounding promotes keratinocyte and epithelial cell migration 9,23 , however, the ERK pathway is involved in the wound healing process through promotion of cell proliferation but not cell migration 24 .…”
Section: Effect Of Bfgf MMC U0126 and Fcs On Cell Migration And Woumentioning
confidence: 99%